A 3D bioprinted complex structure for engineering the muscle–tendon unit. (17th June 2015) - Merceron, Tyler K; Burt, Morgan; Seol, Young-Joon; Kang, Hyun-Wook; Lee, Sang Jin; Yoo, James J; Atala, Anthony
Abstract: Three-dimensional integrated organ printing (IOP) technology seeks to fabricate tissue constructs that can mimic the structural and functional properties of native tissues. This technology is particularly useful for complex tissues such as those in the musculoskeletal system, which possess regional differences in cell types and mechanical properties. Here, we present the use of our IOP system for the processing and deposition of four different components for the fabrication of a single integrated muscle–tendon unit (MTU) construct. Thermoplastic polyurethane (PU) was co-printed with C2C12 cell-laden hydrogel-based bioink for elasticity and muscle development on one side, while poly( ϵ -caprolactone) (PCL) was co-printed with NIH/3T3 cell-laden hydrogel-based bioink for stiffness and tendon development on the other. The final construct was elastic on the PU-C2C12 muscle side ( E  = 0.39 ± 0.05 MPa), stiff on the PCL-NIH/3T3 tendon side ( E  = 46.67 ± 2.67 MPa) and intermediate in the interface region ( E  = 1.03 ± 0.14 MPa). These constructs exhibited >80% cell viability at 1 and 7 d after printing, as well as initial tissue development and differentiation. This study demonstrates the versatility of the IOP system to create integrated tissue constructs with region-specific biological and mechanical characteristics for MTU engineering.